Changes in Noninsurance and Care Unaffordability Among Cancer Survivors Following the Affordable Care Act. (5th November 2019) - Han, Xuesong; Jemal, Ahmedin; Zheng, Zhiyuan; Sauer, Ann Goding; Fedewa, Stacey; Yabroff, K Robin
Abstract: Background: Little is known about changes in socioeconomic disparities in noninsurance and care unaffordability among nonelderly cancer survivors following the Affordable Care Act (ACA). Methods: Cancer survivors aged 18–64 years nationwide were identified from the Behavioral Risk Factor Surveillance System. Trend and difference-in-differences analyses were conducted to examine changes in percent uninsured and percent reporting care unaffordability pre–(2011 to 2013) and post–(2014 to 2017) ACA Medicaid expansion, by sociodemographic factors. Results: A total of 118 631 cancer survivors were identified from Medicaid expansion (n = 72 124) and nonexpansion (n = 46 507) states. Following the ACA, percent uninsured and percent reporting care unaffordability decreased nationwide. Medicaid expansion was associated with a 1.8 (95% confidence interval [CI] = 0.1 to 3.5) percentage points (ppt) net decrease in noninsurance and a 2.9 (95% CI = 0.7 to 5.1) ppt net decrease in care unaffordability. In stratified analyses by sociodemographic factors, substantial decreases were observed in female survivors, those with low or medium household incomes, the unemployed, and survivors with multiple comorbidities. However, we observed slightly increased percentages in reporting noninsurance (ppt = 1.7; 95% CI = −1.2 to 4.5) and care unaffordability (ppt = 3.1, 95% CI = −0.4 to 6.5) in nonexpansion states between 2016 and 2017, translating to 67 163 and 124 160 survivors, respectively. Conclusion: We observed reductions in disparities by sociodemographic factors in noninsurance and care unaffordability among nonelderly cancer survivors following the ACA, with largest decreases in women, those with low or medium income, multiple comorbid conditions, the unemployed, and those residing in Medicaid expansion states. However, the uptick of 82 750 uninsured survivors in 2017, mainly from nonexpansion states, is concerning. Ongoing monitoring of the effects of the ACA is warranted, especially in evaluating health outcomes.